Learning Circuit Methods in Maintaining Physical Fitness : Literature Review - Adingnusi Adingnusi; Nanik Indahwati; Anung Priambodo (Universitas STRADA Indonesia, 2021)
This research uses literature review method with technical literature using a synthesis matrix. The synthesis matrix is a review technique using a table consisting of columns of reference sources, samples, methods, interventions, and findings. The literature referred to comes from previous research journals published from 2011-2021. Previous research journals were selected based on the focus of learning the circuit method in maintaining physical fitness, so that the keyword search for the journal was based on learning the circuit method or teaching circuit method. The referred journal pages come from google schoolar, science direct and researchgate. The results of this study indicate that there are 7 national journals and 1 international journal that have been reviewed based on reference sources, types of samples, research methods, given interventions to the findings about learning the circuit method in maintaining physical fitness.